PERBEDAAN POLA ASUH BAHASA ANAK ANTARA IBU INFLUENCER SHABIRA ALULA DAN IBU GENERASI MILENIAL-GENERASI Z - Aulia Diva Dry Anindia; Vivia Yazna; Fanny Nur Apriliany; Rima Ayu Apriliani; Iis Lisnawati (LPPM Universitas Cipta Mandiri, 2025)
Advances in digital technology have influenced the way parents guide their children's language skills, especially through the increasingly strong role of social media in daily life. This study aims to analyze the differences in parenting patterns between a mother who is known as a public figure on social media and two mothers from different generations, in order to support children's language development in the digital era. The method used is descriptive qualitative with data collection techniques through interviews and observations of three informants, each representing a public figure on social media, millennial generation, and generation Z. The results show that public figures on social media are more likely to have different parenting patterns. The results showed that public figures on social media apply parenting patterns that emphasize the use of formal and polite language consistently. Mothers from the millennial generation are more flexible and allow the use of nonstandard language as long as they maintain politeness. Meanwhile, z-generation mothers combine assertiveness and freedom, teach sensitivity to the context of language use and limit their children's access to social media. The study concludes that parenting patterns are strongly influenced by generational background, personal values and the development of digital technology.